Pengaruh Model Pembelajaran Berbasis Teknologi Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Akidah Akhlak di SMP Muhammadiyah 8 Surakarta Tahun Pelajaran 2024/2025 - Aisyah Az Zahra; Muhammad Jafar Nashir (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to: (1) identify the extent of the use of information technology-based learning media at Muhammadiyah 8 Junior High School Surakarta in the 2024/2025 academic year, (2) determine students’ critical thinking skills in the Akidah Akhlak subject, and (3) examine the influence of technology-based learning models on students’ critical thinking skills. The research employed a quantitative correlational method with a population of 30 students from class IT 1. Data collection techniques included observation, questionnaires, and documentation. Data analysis used the Pearson Product Moment correlation test.The findings reveal that: (1) the implementation of technology-based learning is categorized as